Research of Resilient Kitchen Space Storage Based on the Sustainability Perspective - Cheng, Rao; Zhao, Shenyang; Cui, Shijia; Huang, Jiayi; Wang, Xiang (Journal of Research in Science and Engineering, 2025)
Accelerated urbanization and improved living standards have brought attention to kitchen space utilization and sustainability. This paper explores innovative designs to achieve Resilient kitchen storage, improve space utilization and resource saving. The feasibility of the design solution is evaluated through comparative analysis and user research. Resilient kitchen storage strategies based on sustainable development are proposed to provide reference for future design.